2009
DOI: 10.1080/17429140902898429
|View full text |Cite
|
Sign up to set email alerts
|

Sucrose synthase levels do not limit or regulate carbon transfer in the arbuscular mycorrhizal symbiosis

Abstract: Sucrose synthase (SuSy) is the main sucrose breakdown enzyme in plant sink tissues, including nodules, and is a possible candidate for the diversion of plant carbon to arbuscular mycorrhizal (AM) fungi in roots. We tested the involvement of SuSy in AM symbiosis of Glomus intraradices and Pisum sativum (pea). We observed that peas deficient in the predominant root isoform of SuSy were colonized successfully by AM fungi similar to wild-type roots. SuSy protein levels did not increase in roots as AM symbiosis dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…It was suggested that Susy activity might be essential for nitrogen fixation in root nodules, due to the low-oxygen environment in the nodules (Gordon et al, 1999). Interestingly, the mutation did not appear to affect the plant’s symbiotic relationship with arbuscular mycorrhizae (Yarnes and Sengupta-Gopalan, 2009).…”
Section: Other Roles Of Susymentioning
confidence: 99%
“…It was suggested that Susy activity might be essential for nitrogen fixation in root nodules, due to the low-oxygen environment in the nodules (Gordon et al, 1999). Interestingly, the mutation did not appear to affect the plant’s symbiotic relationship with arbuscular mycorrhizae (Yarnes and Sengupta-Gopalan, 2009).…”
Section: Other Roles Of Susymentioning
confidence: 99%